Evaluation of anticataleptic activity of Hydroxytyrosol on Haloperidol induced Catalepsy in Experimental Animal - Bansode, Mira T; Chaware, V. J; Redasani, V. K (Asian Journal of Pharmaceutical Research and Development, 2021)
Catalepsy is a symptom resulting from problems with the nervous system, and causes muscular rigidity. People with the symptoms may also be less sensitive to touch and have a decreased sensitivity to pain. Catalepsy generally causes people to be unresponsive to speech. It is similar to catatonia, a condition marked by strange movements, lack of movement, and/or general non responsiveness. However, it typically has an underlying physiological cause and does not cause stereotyped movements.